2013
DOI: 10.1093/icvts/ivt221
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for secondary spontaneous pneumothorax: risk factors for recurrence and morbidity

Abstract: Surgical treatment in patients with SSP had favourable results. Treatment in which the base of the bulla cannot be definitely shut off with staplers is associated with increased morbidity. Significant emphysematous change on preoperative computed tomography image and pulmonary fibrosis are predictors of recurrence. Patients with these findings should be investigated in terms of the indications of surgery and additional treatment, not only bullectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 20 publications
3
62
1
Order By: Relevance
“…The postoperative recurrence rates were reported to range from 0% to 16% (18)(19)(20)(21)(22). In this study, we performed surgeries in carefully selected 46 (21.3%) out of the total 216 consecutive cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The postoperative recurrence rates were reported to range from 0% to 16% (18)(19)(20)(21)(22). In this study, we performed surgeries in carefully selected 46 (21.3%) out of the total 216 consecutive cases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in recent years, age alone has not been used as a criterion for any type of surgery for SSP. Several studies have shown favorable outcomes by applying the surgical principle of minimal repair in elderly patients with SSP (20,21,23,24). Surgeries following this principle aim to excise only the targeted, active leakage point, and avoid performing a bullectomy of thick-walled bullae or a lung-volume-reduction surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with minor emphysema and pneumothorax, pleural tenting might contribute equally to the recovery as wedge resection of the diseased lung parenchyma and pleurodesis. Patients with severe emphysema are often comorbid with pneumonia and respiratory failure, and cardiovascular complications (12)(13)(14), which significantly prolong the hospital stay. Nonetheless, the removal of chest tube often indicated the elimination of residual pleural space and persistent air leak, and the expanded lung parenchyma with improved gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…8) After blebs and bullae occur from the degradation of elastic fibres, an increase in alveolar pressure due to small airway obstructions ruptures them, resulting in spontaneous pneumothorax. 2) This mechanism often deteriorates the alveolar structure at the base of blebs and bullae, 1) and this structure, known as a reticulated trabecula-like structure, 1) is well recognized as emphysema in secondary spontaneous pneumothorax (SSP); 9) however, it has not been investigated in PSP. Emphysema has been reported to be associated with the recurrence of SSP after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Emphysema has been reported to be associated with the recurrence of SSP after surgery. 9) We assumed that the reticulated trabecula-like structure in PSP would be involved in postoperative air leakage after VATS bullectomy.…”
Section: Introductionmentioning
confidence: 99%